SYNTHETIC AND NATURAL FE-MAG CHLORITOID: STRUCTURAL, SPECTROSCOPIC AND THERMODYNAMIC STUDIES - Koch-Müller M.; Wirth R.; Gottschalk M.; Abs-Wurmbach I.; Langer K.; Shaw C. (My University, 2000)
Fe-Mg bearing chloritoids were synthesized at 18-35 kbar and 590-720 degrees C in a piston cylinder apparatus under the f(O2) defined by the Fe/FeO buffer (IW). We investigated the synthetic crystals by electron microprobe, X-ray powder diffraction, high-resolution transmission electron microscopy, Mossbauer spectroscopy and diffuse reflectance spectroscopy in the UV-MR (30000-6000 cm(-1)). Structural studies reveal that the high-pressure chloritoids crystallize in the triclinic space group C1. The molar volume of the chloritoid solid solutions depends linearly on composition. The crystal lattices are nearly perfect with almost no defects, while some of the triclinic chloritoids may contain minor amounts of monoclinic intergrowths. Mossbauer spectroscopy shows that in the synthetic chloritoids a small amount of Fe-tot is incorporated as Fe3+. This result is consistent with estimates from electron microprobe analyses and the results of diffuse reflectance spectroscopy. The diffuse reflectance spectra exhibit a broad band at about 15000 cm(-1) caused by Fe2+Fe3+ charge transfer and two small crystal-field bands at about 11000 and 8200 cm(-1) due to Fe2+ in the strongly distorted M1B octahedron (H (a) over circle lenius et al., 1981). The crystal-field effect on Delta H-excess (CFSEexcess) of Fe2+ in chloritoid was determined by an analysis of the crystal-field spectra. CFSEexcess is negative within the whole Fe-Mg chloritoid solid-solution series. It is larger in the Fe-rich than in the Mg-rich part of the system, which indicates a non-ideal, asymmetrical mixing behaviour of Fe-Mg chloritoid.